Penanganan Hipertermia Pada Anak Dengan Demam Tifoid Di Rsud Pandan Arang Boyolali - Putri, Noviana, Endang Zulaicha S , S.Kp (2016)
Introduction: Typhoid fever is an infectious disease that is transmitted through food and water contaminated with Salmonella Typhi bacteria. Typhoid fever patients experienced a rise in temperature in the first week, declining in the morning and rose again in the afternoon and evening. Hyperthermia is a condition where the body temperature exceeds the set point (set point) over 37ºC caused by external conditions or the body which creates more heat that can be released by the body. Hyperthermia if left untreated can cause dehydration which will disrupt electrolyte balance and can cause seizures. Recurrent seizures can cause brain cell damage that can lead to behavioral disturbances of children and severe dehydration can cause shock and can be fatal to lead to death. Warm compresses action is one of the independent actions of nurses to deal with hyperthermia. A warm compress is coating the surface of the skin with a towel that has been soaked in warm water with a temperature of 30oC-35oC. Objective: to determine and implement the handling of hyperthermia in children with typhoid fever according to the standard of nursing. Methods: The method used in preparing a scientific paper is a description method, the case study approach taken in the ward Edelweiss Pandan Arang Boyolali District Hospital on March 29, 2016 until April 1, 2016. Data obtained by the patient's mother, nurses, medical teams, records nursing, and a doctor's note. Result: after the act of nursing for 3x24 hours of the patient's body temperature within normal range. Conclusion: from hyperthermia treatment is performed in children with typhoid fever during 3x24 hours showed that the patient's temperature returned to normal and there is no increase in temperature in the afternoon and evening.